Validation of the PHQ-9 as a screening instrument for depression in diabetes patients in specialized outpatient clinics - van Steenbergen-Weijenburg Kirsten M; de Vroege Lars; Ploeger Robert R; Brals Jan W; Vloedbeld Martijn G; Veneman Thiemo F; Hakkaart-van Roijen Leona; Rutten Frans FH; Beekman Aartjan TF; van der Feltz-Cornelis Christina M (BMC, 2010)
Abstract Background For the treatment of depression in diabetes patients, it is important that depression is recognized at an early stage. A screening method for depression is the patient health questionnaire (PHQ-9). The aim of this study is to validate the 9-item Patient Health Questionnaire (PHQ-9) as a screening instrument for depression in diabetes patients in outpatient clinics. Methods 197 diabetes patients from outpatient clinics in the Netherlands filled in the PHQ-9. Within 2 weeks they were approached for an interview with the Mini Neuropsychiatric Interview. DSM-IV diagnoses of Major Depressive Disorder (MDD) were the criterion for which the sensitivity, specificity, positive- and negative predictive values and Receiver Operator Curves (ROC) for the PHQ-9 were calculated. Results The cut-off point of a summed score of 12 on the PHQ-9 resulted in a sensitivity of 75.7% and a specificity of 80.0%. Predictive values for negative and positive test results were respectively 93.4% and 46.7%. The ROC showed an area under the curve of 0.77. Conclusions The PHQ-9 proved to be an efficient and well-received screening instrument for MDD in this sample of diabetes patients in a specialized outpatient clinic. The higher cut-off point of 12 that was needed and somewhat lower sensitivity than had been reported elsewhere may be due to the fact that the patients from a specialized diabetes clinic have more severe pathology and more complications, which could be recognized by the PHQ-9 as depression symptoms, while instead being diabetes symptoms.